Effect of institutional factors on stock market development in Asia. (18th August 2008) - Gani, Azmat; Ngassam, Christopher
This paper examines the links between institutional factors and stock market development in a sample of eight Asian countries with developing as well as mature stock markets. Five indicators of institutional quality are chosen: government effectiveness, rule of law, regulatory quality, control of corruption and political stability, together with some control variables. Our estimation procedure, utilising three different estimation methods, including the fixed effects model correcting for AR (1) errors, produced consistent results. The results obtained here provide strong evidence that economic growth, diffusion of technology, rule of law and political stability positively aid Asia's stock market expansion. On the other hand, poor regulatory quality and government effectiveness seem to be working against Asia's stock market development. Our results support the proposition that institutional quality is an integral part of enhancing the development of stock markets in a country. Thus, institutional quality matters for stock market development.